Scientific Inquiry and Concept Mastery in Grade 10: Teaching Practices in Junior High School Science at Eastern Potia National High School - Linglingon, Jayne Ruth (Studies in Technology and Education, 2026)
Scientific inquiry is a core component of effective science education, fostering learners’ conceptual understanding, critical thinking, and problem-solving skills. In the Philippine K–12 curriculum, Junior High School Science emphasizes inquiry-based learning to support meaningful concept mastery. However, implementing inquiry-oriented instruction in rural public schools presents unique challenges. This study examined the teaching practices employed in Grade 10 Science at Eastern Potia National High School, with particular focus on how scientific inquiry supports learners’ concept mastery. Using a qualitative case study design, data were collected through semi-structured teacher interviews, classroom observations, and document analysis. Thematic analysis revealed two major themes: learner-related challenges affecting inquiry and concept mastery, and inquiry-oriented teaching practices adopted by science teachers. Findings indicate that while learners face difficulties related to prior knowledge gaps, limited resources, and low confidence in scientific reasoning, teachers employ adaptive inquiry strategies such as guided experimentation, contextualized activities, and scaffolded questioning to promote conceptual understanding. The study underscores the importance of sustained instructional support, teacher professional development, and context-responsive inquiry approaches to strengthen science learning in rural Junior High School settings.